Association of ABO polymorphisms and pancreatic Cancer/ Cardiocerebrovascular disease: a meta-analysis - Yanxia Li; Luyang Liu; Yubei Huang; Hong Zheng; Lian Li (BMC, 2020)
Abstract Background ABO gene polymorphisms have been reported to be associated with the risk of multiple cancers and cardiocerebrovascular diseases. However, the results remained controversial. In this study, we conducted a systematic review and meta-analysis to clarify the association between two SNPs (rs505922 and rs657152) in ABO gene and cancers/cardiocerebrovascular diseases. Method All eligible case-control studies come from PubMed, Embase and Web of Science up to Jan. 1, 2019. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the corresponding associations. Sensitivity analysis, publication bias assessment, and heterogeneity test were performed using STATA 12.0. Results A total of nineteen articles involving twenty-two case-control populations were included according to inclusion and exclusion criteria. Twelve populations (20,820 cases and 27,837 controls) were used to evaluate the relationship between rs505922 and overall cancers and nine populations (22,275 cases and 71,549 controls) were included to assess the association between rs505922 and cardiocerebrovascular diseases. The results showed a significant association between the rs505922 polymorphism and cancers (CvsT: OR = 1.13, 95%CI = 1.05-1.22, P = 0.001), and cardiocerebrovascular diseases (OR = 1.36, 95%CI = 1.19-1.57, P < 0.001). Five populations (8660 cases and 10,618 controls) were included to evaluate association between rs657152 and cancers and five populations (8105 cases and 6712 controls) were included to estimate the relationship between rs657152 and cardiocerebrovascular diseases. The result of meta-analysis reveals that rs657152 was significantly associated with cancers (OR = 1.18, 95%CI = 1.13-1.23, P < 0.001) and cardiocerebrovascular diseases (OR = 1.54, 95%CI = 1.24-1.92, P < 0.001). Conclusion Our study suggested that ABO polymorphisms might serve as a risk factor of pancreatic cancers and cardiocerebrovascular diseases.